Evaluation of the environmental polio surveillance system-Northern Region, Ghana, 2021. - Benjamin Baguune; Eunice Baiden Laryea; Joseph Asamoah Frimpong; Samuel Dapaa; Kwame Kodom Achempem; Ernest Kenu; Dennis Odai Laryea (PLoS ONE, 2024)
Background Acute Flaccid Paralysis (AFP) surveillance is the gold standard in the polio eradication initiative. The environmental component of polio surveillance can detect circulating Polioviruses from sewage without relying on clinical presentation. The effectiveness of the Environmental Surveillance (ES) is crucial to global polio eradication. We assessed the usefulness and attributes of the ES system in the Northern region and determined if the system is meeting its objectives. Methods We conducted a descriptive cross-sectional evaluation in the Northern region from 2019 to 2020 using the updated US Centers for Disease Control and Prevention guideline. We interviewed stakeholders, reviewed records, and observed surveillance activities from 29th March to 7th May, 2021. Quantitative data were analyzed manually as frequencies and proportions whiles thematic analysis was used for the qualitative data. Results One of 48 (2.1%) samples collected tested positive for circulating vaccine-derived Poliovirus (cVDPV). The cVDPV detection triggered enhanced AFP surveillance that resulted in the identification of a case of AFP. Three rounds of polio vaccination campaigns were organized. All surveillance officers interviewed were willing to continue providing their services for the ES. Reporting form has few variables and is easy to complete. The completeness of forms was 97.9% (47/48). Samples collected were dispatched on the same day to the testing laboratory. The system's data was managed manually. Conclusion The system was useful in detecting polio outbreaks. Data quality was good, the system was simple, flexible, acceptable, representative, and fairly stable. Sensitivity was high but predictive value positive was low. Timeliness in reporting was good but feedback from the national level could not be assessed. There is a need to improve on the feedback system and ensure that, the surveillance data is managed electronically.